2008
DOI: 10.1158/0008-5472.can-07-6497
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Survival Is Associated with Telomere Length in Peripheral Blood Cells

Abstract: Telomeres are essential for maintaining chromosomal stability. Previous studies have indicated that individuals with shorter blood telomeres may be at higher risk of developing various types of cancer, such as in lung, bladder, and kidney. We have analyzed relative telomere length (RTL) of peripheral blood cells in relation to breast cancer incidence and prognosis. The study included 265 newly diagnosed breast cancer patients and 446 female controls. RTL was measured by real-time PCR, and our results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
163
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(187 citation statements)
references
References 39 publications
(42 reference statements)
21
163
1
Order By: Relevance
“…1A) with a similar magnitude of effect as seen in previous comparable studies (4,24). Longer age-adjusted maternal TL predicted longer offspring TL (Fig.…”
Section: Resultssupporting
confidence: 86%
“…1A) with a similar magnitude of effect as seen in previous comparable studies (4,24). Longer age-adjusted maternal TL predicted longer offspring TL (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Recently, Svenson et al 27 showed that telomere length in peripheral blood cells differs between breast cancer patients and control subjects, and may serve as a significant prognostic biological marker. In general, malignant tumors show shorter telomeres than corresponding normal tissue, and telomere dysfunction has been indicated as a negative prognostic marker in solid tumors, including breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42][43][44] Short telomeres are not only a by-product of tumor development. In fact, telomeric loss could be instrumental in maximizing the malignant potential of tumor cells by boosting genetic instability and by interfering epigenetically with genes located in subtelomeric regions.…”
Section: Discussionmentioning
confidence: 99%